Procedimento para avaliação emergética na despoluição de rios urbanos – análise emergética de córregos do programa córrego limpo em São Paulo - Flausino, Fabio Richard (2023)
The use of emergy indicators to evaluate complex processes such as the depollution of urban rivers aims to contribute to a better use and preservation of resources, in addition to valuing the ecosystem services provided by the body of water. Given this context, a bibliometric and systematic review was carried out that identified the absence of the use of emergy indicators in the process of depollution of urban rivers. Therefore, the objective of this work is to provide an emergy evaluation procedure for the depollution process of urban rivers that allows technicians, academics, and managers of urban river revitalization processes to improve monitoring and decision-making directly related to the process. It is concluded that an evaluation procedure based on emergy contributes with a theory in the development of new scientific analyzes applied in processes of urban revitalization and nature preservation based on the realization of a multiple case study. The application of this evaluation procedure contributes to society in improving the provision of public resources and in the effective maintenance of urban rivers that provide ecosystem services to all interested parties (residents, granting authority and sanitation company). In practice, the multiple case study applied in five streams that were depolluted in the first of the clean stream program shows the effectiveness of the use of emergy indicators demonstrating the improvement of sustainability in the region and contributing contributions to all those interested in the efficiency of the water supply stage. resources and the quality of the local environment. The use of this new assessment helps in monitoring the depollution process from the beginning, demonstrating the sustainability of the process to support resources and maintain the method of water body to be depolluted.